2016
DOI: 10.1111/jppi.12161
|View full text |Cite
|
Sign up to set email alerts
|

Development of Self‐Help, Language, and Academic Skills in Persons With Down Syndrome

Abstract: Using visual analysis by means of scatterplots, correlational analysis, and linear regressions, the authors explored the skills of individuals with Down syndrome in the areas of self‐help, language, academics, and computer skills. By combining data of several Dutch studies, they obtained 1,252 different observations made by parents on 862 individuals, aged <1–35 years. Research shows advancement in language skills up to the age of 12, with plateauing afterward. In contrast, self‐help skills still increase in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In contrast to our hypotheses, no sex differences were observed in these rates over time. Prior work examining skills such as adaptive functioning, receptive vocabulary, and grammatical abilities suggests variable patterns of development in DS, with reduced predictive relationships between age and ability, or even declines in later adolescence and adulthood (Cuskelly, Povey & Jobling, 2016; de Graaf & de Graaf, 2016; Dykens et al, 2006). Perhaps, then, current results reflect a more general tendency during school age for pragmatic abilities of individuals with DS to stabilize.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our hypotheses, no sex differences were observed in these rates over time. Prior work examining skills such as adaptive functioning, receptive vocabulary, and grammatical abilities suggests variable patterns of development in DS, with reduced predictive relationships between age and ability, or even declines in later adolescence and adulthood (Cuskelly, Povey & Jobling, 2016; de Graaf & de Graaf, 2016; Dykens et al, 2006). Perhaps, then, current results reflect a more general tendency during school age for pragmatic abilities of individuals with DS to stabilize.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, comparing pragmatic growth of children with DS to mental-age matched TD controls on a standardized measure of pragmatic language that involves making pragmatic language judgments (the Comprehensive Assessment of Spoken Language-Pragmatic Judgment Subscale), G. E. Martin et al (2013) reported that boys with DS demonstrated greater difficulties on vocabulary, syntax, and pragmatic language and developed these skills at a slower rate than TD boys of similar nonverbal mental age. There are mixed findings overall regarding changes in rates of development of other abilities across age periods in DS, with some studies suggesting “plateaus” in development and other suggesting no differences in rates of development between preschool and adult years (Cuskelly, Povey, & Jobling, 2016; Dykens et al, 2006; de Graaf & de Graaf, 2016). This suggests a continued need for research on longitudinal development of pragmatic language in DS, examining different types of pragmatic skills with a particular focus on comparison groups and assessment methods employed.…”
mentioning
confidence: 99%
“…This was also observed in an Australian group with DS-individuals born between 1971 and 1978 compared to historical data from the UK and the U.S. [ 29 ]. In the Netherlands, a shift toward school inclusion took place later in the 1990s, showing improved academic outcomes despite lower cognitive skills due to regular educational settings [ 30 ]. Self-help was acquired until young adulthood, whereas computer skills showed generational differences.…”
Section: Discussionmentioning
confidence: 99%
“…In order to select the results relevant to our target group, we took into account the information provided by the studies on the severity of the disability. Only one study (Dessemontet, Bless, & Morin, 2012) referred to standardised measures (IQ), while three other studies (de Graaf & de Graaf, 2016;de Graaf & van Hove, 2015;Ferreira, Aguiar, Correia, Fialho, & Pimentel, 2017) reported measures derived from non-standardised instruments (e.g. Abilities Index declared by teachers, IQ reported by parents, IQ in different areas declared by parents and teachers).…”
Section: Contexts Of Inclusion and Participantsmentioning
confidence: 99%
“…difficulties in communicating with peers and teachers). Three studies compared adaptive skills of students with MSCD in special and inclusive settings (de Graaf & de Graaf, 2016;Dessemontet et al, 2012;Hardiman et al, 2009) using quantitative data collection. According to Dessemontet et al (2012), outcomes in global adaptive behaviours were greater for students attending inclusive settings compared to those students attending special education; likewise in computer skills and language, as reported by de Graaf and de Graaf (2016).…”
Section: Learning Outcomesmentioning
confidence: 99%